Serology reveals comparable patterns in the transmission intensities of Plasmodium falciparum and Plasmodium vivax in Langkat district, North Sumatera Province, Indonesia - Lubis, Inke Nadia Diniyanti; Nainggolan, Irbah Rea Alvieda; Meliani, Meliani; Hasibuan, Beby Syofiani; Sangaran, Kumuthamalar; Samsudin, Luqman; Chuangchaiya, Sriwipa; Divis, Paul Cliff Simon; Permatasari, Ranti; Idris, Zulkarnain Md (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe incidence of malaria in Indonesia has declined significantly over the last few decades. Thus, a demand for more sensitive techniques to describe low levels of transmission in the country is important. This study was conducted to evaluate antibody response to Plasmodium falciparum and Plasmodium vivax in an area nearing elimination in North Sumatera Province, Indonesia.MethodsA cross-sectional survey was conducted in Langkat district, North Sumatera Province, in June 2019. Basic demographic data and filter paper blood spots were collected from 339 participants. Antibody responses to two P. falciparum (PfAMA-1 and PfMSP-119) and two P. vivax (PvAMA-1 and PvMSP-119) antigens were measured using indirect enzyme-linked immunosorbent assay (ELISA). Seroconversion rates (SCR) were estimated by fitting a simple reversible catalytic model to seroprevalence data for each antibody. Multiple logistic regression was used to investigate factors associated with exposure.ResultsThe overall malaria seroprevalence was 10.6% for PfAMA-1, 13% for PfMSP-119, 18.6% for PvAMA-1, and 7.4% for PvMSP-119. Seropositive individuals for P. falciparum (PfAMA-1/PfMSP-119) and P. vivax (PvAMA-1/PvMSP-119) were similar at 20.7%, with no significant differences observed between age groups (p > 0.05). Based on the reversible catalytic model, the calculated SCRs indicated a higher level of P. falciparum transmission than P. vivax using all tested antigens. In the adjusted model, only spending nights in the forest was associated with P. vivax seropositivity (odd ratio: 3.93, p < 0.001).ConclusionThe analysis of community-based serological data helps describe the similar levels of P. falciparum and P. vivax transmission in the Langkat district. The use of a serological approach enhances the detection of past exposure, aiding in the identification of epidemiological risk factors and malaria surveillance in low transmission settings in Indonesia.